PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF KOPUTANG “KOTAK PINTAR ULAR TANGGA” MATERI OPERASI HITUNG BILANGAN CACAH SISWA KELAS IV SEKOLAH DASAR KHASANAH SAMARINDA - Najelia Ayu Nurosida; Andi Asrafiani Arafah; Makmun; Sukriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics learning in elementary schools still faces various challenges, particularly the low interest and motivation of students in understanding whole number operations, as well as the lack of learning media in the process. This condition demands innovation in instructional media that can create an active, enjoyable, and effective learning atmosphere. This research developed an interactive learning medium called Koputang (Smart Snakes and Ladders Box) to examine the development process, feasibility, practicality, and effectiveness of the medium in improving the learning outcomes of fourth-grade students at SD Khasanah Samarinda. This study draws on the theory of game-based learning and the concept of interactive media, which supports students’ cognitive, affective, and psychomotor engagement. The development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, expert validation questionnaires (media, material, and language),teacher, and student response questionnaires. The validation results showed that the Koputang medium received an average score of 89% (highly feasible) from experts, covering content, appearance, and language aspects. The practicality of the medium was demonstrated through teacher responses of 84% and student responses of 92.6%, both categorized as highly practical. These findings prove that the Koputang medium not only enhances students’ understanding of whole number operations but also creates a more enjoyable, interactive, and meaningful learning experience.